Stigma experiences and adaptations in accessing healthcare services among hill tribes in Thailand: A qualitative study - Peeradone Srichan; Tawatchai Apidechkul; Ratipark Tamornpark; Thanatchaporn Mulikaburt; Pilasinee Wongnuch; Siwarak Kitchanapaibul; Panupong Upala; Chalitar Chomchoei; Fartima Yeemard; Anusorn Udplong; Onnalin Singkhorn (PLoS ONE, 2025)
Background One of the significant barriers to accessing healthcare services is the stigma experienced from healthcare workers. Individuals can be significantly impacted by stigma owing to being classed according to particular characteristics, such as being tribal members. This study aimed to understand the experiences and adaptations of hill tribe people in Thailand, who face stigma when accessing healthcare services. Methods A qualitative phenomenological method was used to elicit information from hill tribe members with prior experience accessing healthcare. A question guide was used to interview the participants. The interviews were conducted in private and confidential rooms in hill tribe villages in August 2021. Each interview lasted for 45 minutes. Results A total of 85 people participated in the study: 25 men and 60 women. The Akha and Lahu people constituted the majority of the participants. Many had no education, and the average monthly income was 2,500 baht per family. Three forms of stigma were detected among hill tribe people accessing healthcare services in different hospitals: verbal stigma, physical stigma, and contempt. Three levels of impact were found: completely not understood with no effect, little understanding with little pain, and fully understood with full impact. Two reactions to stigma were identified: nonresponse and response (proper, nonproper immediate response and assertive response). Three factors were protective against stigma: speaking fluent Thai, wearing modern clothing, and the ability to pay medical fees. Conclusions Hill tribe people face several forms of stigma related to various levels of impact and different reaction approaches. Some factors can protect against encountering stigma while accessing healthcare services in hospitals. The implementation of programs to reduce stigma should focus on improving the understanding of people’s different cultures and languages and effective communication skills for hill tribe people. The central government of Thailand should develop a national strategic plan to improve these socioeconomic statuses.